The state, war, and the state of war - Holsti, K. J. 1935- (Cambridge ; Cambridge University Press, 1996)
War has traditionally been studied as a problem deriving from the relations between states. Strategic doctrines, arms control agreements, and the foundations of international organizations such as the United Nations, are designed to prevent wars between states. Since 1945, however, the incidence of interstate war has actually been declining rapidly, while the incidence of internal wars has been increasing.
The author argues that in order to understand this significant change in historical patterns, we should jettison many of the analytical devices derived from international relations studies and shift attention to the problems of "weak" states: those states unable to sustain domestic legitimacy and peace. This book surveys some of the foundations of state legitimacy and demonstrates why many weak states will be the locales of war in the future.
Finally, the author asks what the United Nations can do about the problems of weak and failed states.
Includes bibliographical references and index.
Keywords: War; Legitimacy of governments